2015
DOI: 10.1063/1.4913216
|View full text |Cite
|
Sign up to set email alerts
|

Competitive effects between stationary chemical reaction centres: A theory based on off-center monopoles

Abstract: The subject of this paper is competitive effects between multiple reaction sinks. A theory based on off-center monopoles is developed for the steady-state diffusion equation and for the convection-diffusion equation with a constant flow field. The dipolar approximation for the diffusion equation with two equal reaction centres is compared with the exact solution. The former turns out to be remarkably accurate, even for two touching spheres. Numerical evidence is presented to show that the same holds for larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The question to be addressed now is how to use the single-sphere's concentration field to model competitive effects between two (or more) spheres. A brief review is given below of the methodology developed in our previous paper [6]. A crucial ingredient in this method is the knowledge of a Green's function for the corresponding equation.…”
Section: 2mentioning
confidence: 99%
See 4 more Smart Citations
“…The question to be addressed now is how to use the single-sphere's concentration field to model competitive effects between two (or more) spheres. A brief review is given below of the methodology developed in our previous paper [6]. A crucial ingredient in this method is the knowledge of a Green's function for the corresponding equation.…”
Section: 2mentioning
confidence: 99%
“…In a recent paper [6] we developed an approximate analytical theory for such a system in the case of pure diffusion and in the case of diffusion combined with a relatively weak convective component. It was found that the range of applicability of the former theory in the convection-diffusion (CD) case was very limited; beyond Péclet numbers of about 0.6, our theory was found to be unreliable.…”
Section: Ams Subject Classifications 76r50 76m45mentioning
confidence: 99%
See 3 more Smart Citations